Lafaz Al Bai’u Mistlu Al Riba dalam Surah Al Baqarah Ayat 275 - Zainuddin, Zainuddin; Zainuddin, Anayya Syadza (Forum Intelektual Qur'an dan Hadits Asia Tenggara (SEARFIQH) Kota Banda Aceh, 2022)
This paper discusses the views of the commentators on the lafadz al-bai'u mitslu al-riba in surah al-Baqarah verse 275. Some commentators interpret the word amtsal, as tasybih and majaz, and others interpret it as i'jaz. This paper uses the method of interpretation of tahlili, through the approach of the field of amtsal al-Qur'an, literature research. The main sources are the books of tafsir, with the aim of studying and knowing the lafadz al-bai'u mitslu al-riba according to the mufassirs. So that the economic principles of monotheism, humanity, justice and peace were developed. The conclusion of this article is that Allah deliberately raised the parable of the ignorant, because socio-cultural Arab society and humans in general have a culture that is difficult to abandon the practice of usury until now, even building the image of tasybih maqlūb style that usury and buying and selling are the same in terms of taking more profit.ABSTRAKTulisan ini membicarakan pandangan para mufassir tentang lafadz al-bai’u mitslu al-riba dalam surah al-Baqarah ayat 275. Sebahagian mufassir menafsirkan lafaz amtsal, sebagai tasybih dan majaz, dan lainya memaknai dengan i’jaz. Tulisan ini menggunakan metode penafsiran tahlili, melalui pendekatan bidang amtsal al-Qur’an, penelitian kepustakaan. Sumber utama adalah kitab-kitab tafsir, dengan tujuan untuk mengkaji dan mengetahui lafadz al-bai’u mitslu al-riba menurut para mufassir. Sehingga terbangun prinsip ekonomi ketauhidan, kemanusiaan, keadilan dan kedamaian. Kesimpulan tulisan ini sengaja Allah mengangkat kembali perumpamaan kaum jahiliyah, Sebab secara sosio kultural masyarakat Arab dan manusia pada umumnya memiliki budaya yang sulit meninggalkan praktik riba hingga sekarang, bahkan membangun image gaya tasybih maqlūb bahwa riba dan jual beli itu sama dari segi mengambil nilai lebih keuntungan.